Evaluasi Desain Bangunan Berdasarkan Sistem Sertifikasi DGNB (Studi Kasus : The Khabele School, Austin) - Dady Wicaksono; Sugini Sugini (ARSITEKTURA, 2021)
The air pollution problem had become a big problem for many cities in the world. In line with the rapid development of these cities, the concept of sustainability also continues to develop with various solutions to overcome existing problems. To solve the air pollution problem, the authors evaluated the selected building object, The Khabele School, to see the extent of the building's contribution to overcoming the air pollution problem.  The evaluation was carried out based on the DGNB (German Sustainable Building Council) certification system, the variables measured were biotope area factor (BAF), indoor air quality, daylight factor, and zero-carbon mobility. The results reveal that indoor air quality and daylight factors could meet the desired standards, while BAF and zero-carbon mobility had not met the standard. Based on theoretical and empirical studies, this paper discussed alternative design strategies, to improve the quality of the building, so that they can contribute more to overcoming air pollution problem.